Analysis of the Functions of KIT IPA to Support the Independent Curriculum in SDN 1 Cicadas, Bogor Regency - Hayu, Wiworo Retnadi Rias; Ambarwati, Shella; Mawardini, Annissa; Suherman, Irman; Prasetyo, Teguh (Didaktika Tauhidi: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
Props have an important role in achieve a learning goal. Inside props science learning can be in the form of an Integrated Instrument Component (KIT). The challenge of the independent curriculum is that learning facilities are still lacking, and learning resources are incomplete, while the goal in implementing the Independent Curriculum is to train students' soft skills through various school and learning activities. SDN 1 Cicadas already has several Science KITs, but it turns out that the teachers are not optimally using teaching aids when learning Science. This study aims to find out how the Science KIT functions in supporting the Merdeka Curriculum. Data collected using a qualitative approach to the case study method with observation techniques, interviews and documentation studies.The final results of this study indicate that the Science KIT functions in helping teachers prepare lessons for Teaching and Learning Activities (KBM) and making it easier for students to understand learning, improving the quality of science teaching and learning in elementary schools especially during this independent curriculum, developing human resource development programs, creating a fun, active, creative and effective science learning atmosphere. From the results of this study it can be concluded that The science kit at SDN 1 Cicadas comes from BOS funds with fairly complete availability. The function of the Science Kit is to improve the quality of teaching and learning, and to assist teachers in teaching and learning. While the advantages of the Science KIT are training accuracy and dexterity, helping and facilitating teachers, the weakness is that the Science KIT is easily damaged if it is never used.